6)\(3.\left(x+1\right)-2^3.2=11\)
\(3\left(x+1\right)-2^4=11\)
\(3.\left(x+1\right)=11+16\)
3.(x+1)=27
x+1=27:3
x+1=9
x=9-1
x=8
Vậy x=8
7) \(180-2.\left(x+5\right)^2=130\)
\(2.\left(x+5\right)^2=180-130\)
2.(x+5)2=50
(x+5)2=50:2
(x+5)2=25
x+5=5 hoặc x+5=-5
x=5-5 x=-5-5
x=0 x=-10
Vậy x=0 hoặc x=-10
1)300-(2x-4).3=150
(2x-4).3=300-150
(2x-4).3=150
2x-4=150:3
2x-4=50
2x=50-4
2x=46
x=46:2
x=23
Vậy x=23
3)x:5-27:5=18
=>(x-27):5=18
x-27=18.5
x-27=90
x=90+27
x=117
Vậy x=117
(x+1)^2.2=32
(x+1)^2=32:2
(x+1)^2=16
=>(x+1)^2=4^2
=>x+1=4
x=4-1
x=3
Vậy x=3
5)\(2^{x+1}=64\)
\(\Rightarrow2^{x+1}=2^6\)
\(\Rightarrow x+1=6\)
x=6-1
x=5
10)2.x+3x+4x=180
x(2+3+4)=180
x.9=180
x=180:9
x=20
Vậy x=20